Exploring the WEP with a pulsed cold beam of antihydrogen - Doser, Michael; Bräunig, Philippe; Oberthaler, Markus K. (Classical and quantum gravity, 2012)
The AEGIS experiment, currently being set up at the Antiproton Decelerator at CERN, has the objective of studying the free fall of antimatter in the Earth’s gravitational field by means of a pulsed cold atomic beam of antihydrogen atoms. Both duration of free fall and vertical displacement of the horizontally emitted atoms will be measured, allowing a first test of the WEP with antimatter.
Gesehen am 28.03.2018